Juvenile offenders before the courts, υπό Max Grunhui, The young delinquent, υπό Sir Cyril Burt, Young offenders, υπό A.M. Carr-Saunders, Unraveling juvenile delinqueney, υπό Sheldon and Eleanor Glueck, The young delinquent in his social setting, υπό Thom - Κορρέ, Ειρήνη (The Greek Review of Social Research, 1970)
[no abstract available]